Application of Planning Blended Learning Based on SWOT Pattern in TeachingLearning Activities of the Isfahan University of Medical Sciences Iran - Bibi Eshrat i Zaman; Hasan Babri (Kerman University of Medical Sciences, 2013)
Background & Objective: Medical education institutions have always been looking for training methods that have high efficiency and effectiveness Thus the present study has been carried out with the aim of identifying the application of blended learning based on the SWOT pattern in Isfahan University of Medical Sciences Isfahan Iran Methods: This was mixed methods and exploratory research The statistical population consisted of all the faculty members students and IT professionals For the samples 39 were selected from faculty members and 102 from students according to stratified random sampling for quantitative research and 10 from IT professionals according to purposive sampling to be interviewed The instruments for collecting data in the quantitative part were the researchermade questionnaire and in the qualitative part the deep semistructured interview Results: The results of the study showed that the areas of weakness and strength in the internal dimension and in the opportunities and threats in the external dimension were statistically significant The views in the area of strengths were similar however they had significant differences in other areas Moreover the advantages and opportunities have been more than disadvantages and threats of blended learning outlook Conclusion: Despite the weaknesses and threats of the blended learning method all participants in this study were optimistic of the prospects of this method in Isfahan University of Medical Sciences